Experience of using non‐specialized unmanned aerial vehicles for aerial surveys in the studies of exogenous geological processes - A. A. Rybchenko; A. V. Kadetova; E. A. Kozyreva; A. A. Yuriev (Геодинамика и тектонофизика, 2019)
The article reviews the experience of aerial surveys using a quadcopter DJI Inspire 1 PRO (unmanned aerial vehicle, UAV) for solving problems of engineering geodynamics. It describes the application of photogrammetry to estimate quantitative parameters of the studied objects, the experience of using UAVs to study flood processes in the Tunka valley (Russia) and erosion structures in the Ulaanbaatar agglomeration (Mongolia). The first UAV‐acquired data on debris flow alluvial fans and elementary drainage basins of erosion structures are presented. The ranges of UAV flight heights were 100–150 m and 1–30 m for local and detailed aerial photography surveys, respectively. Local surveys covered relatively large objects – debris flow alluvial fans and drainage basins. Detailed aerial photography aimed to investigate the granulometric compositions of debris flow deposits and to construct transverse profiles of erosion structures. Processed aerial photos provided a basis for a schematic map showing the distribution of accumu‐ lated debris flow deposits. The granulometric compositions of coarse fractions in the debris flow deposits were de‐ termined. Based on the survey results, 3D models of the fragments of the erosion structures and their cross‐sections were constructed.